2019
DOI: 10.1136/tobaccocontrol-2018-054878
|View full text |Cite
|
Sign up to set email alerts
|

Impact of e-cigarette health warnings on motivation to vape and smoke

Abstract: BackgroundA prevailing hypothesis is that health warnings for electronic cigarettes (e-cigarettes) could drive people away from vaping and towards smoking cigarettes. We consider an alternative hypothesis that e-cigarette warnings discourage both vaping and smoking.MethodsParticipants were a national convenience sample of 2218 US adults who used e-cigarettes, cigarettes or both. In August 2018, we randomised participants to one of three warning types (control text about littering, text-only e-cigarette warning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 64 publications
2
48
0
Order By: Relevance
“…This finding builds on a prior study showing e-cigarette warnings discouraged both vaping and smoking. 47 Future research Strengths of our experiments include the use of a randomised design, measurement of a primary outcome with strong psychometric properties, 49 and creation of realistic stimuli mirroring actual messages from public health organisations. Limitations include the brief exposure to stimuli in an online study, precluding assessment of behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding builds on a prior study showing e-cigarette warnings discouraged both vaping and smoking. 47 Future research Strengths of our experiments include the use of a randomised design, measurement of a primary outcome with strong psychometric properties, 49 and creation of realistic stimuli mirroring actual messages from public health organisations. Limitations include the brief exposure to stimuli in an online study, precluding assessment of behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…This finding builds on a prior study showing e-cigarette warnings discouraged both vaping and smoking. 47 Future research will clarify the extent to which messages have beneficial spillover effects on behavioural outcomes, as well as whether there are any circumstances in which these messages have unintended consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Brewer 8 and colleagues (Editor's choice) conducted a randomised trial to examine whether warnings on Electronic Nicotine Delivery Systems (ENDS) about nicotine and addiction, which do not appear on cigarettes, could induce smoking. They showed that the warnings discouraged vaping, but found no evidence that ENDS warnings encouraged smoking.…”
Section: Richard O'connormentioning
confidence: 99%
“…Compared to other tobacco products, e-cigarettes have a minimal requirement for a warning label [ 61 ]. Warnings of nicotine addiction on e-cigarette packaging can motivate users to quit [ 62 ] and it can be the case with government’s recommended labels. However, warning labels provided by tobacco companies, on the other hand, are shown to be harder to read and understand [ 63 ].…”
Section: Discussionmentioning
confidence: 99%